(untitled) (Bangladesh Journal of Zoology, 2022)
The study was conducted to assess the prevalence of veterinary ectoparasite of cattle and goats in Brahmanpara, Burichong and Debidwar upazila of Comilla district. In total 560 animals (335 cattle and 225 goats) were examined; among them 373 animals (217 cattle and 156 goats) were found to be infested with several species of ectoparasites. Veterinary animals (cattle and goats) in Brahmanpara upazila showed the highest prevalence (71.80%) and lowest intensity (6.19). Debidwar upazila showed lowest prevalence (55.47%) and highest intensity (12.20). Cattle in Brahmanpara showed highest prevalence (78.50%) and lowest intensity (5.59) and Debidwar upazila showed lowest prevalence (43.00%) and highest intensity (13.66). Goats in Debidwar upazila showed highest prevalence and intensity (100% and 9.97, respectively). Burichong upazila showed lowest prevalence (64.22%) and Brahmanpara showed lowest intensity (6.84). The study of ectoparasites is important, not only for livestock but also for humans, since fleas, lice and ticks also parasitize humans, especially those who work in close contact with the affected animals. Therefore, more studies are needed to estimate the economic losses and control measures of veterinary animal parasitic diseases that are caused by ectoparasites. Bangladesh J. Zool. 50 (2): 201-215, 2022